COMPARISON OF RECURRENCE RATE BETWEEN EN BLOC RESECTION OF BLADDER TUMOUR AND CONVENTIONAL TECHNIQUE FOR NON-MUSCLE INVASIVE BLADDER CANCER - Bangash, Muhibullah; Hammad Ather, Muhammad; Khan, Nasir; Mohammad, Shoaib; Uddin, Zeeshan (Journal of Ayub Medical College Abbottabad, 2020)
Background: Conventional transurethral resection of urinary bladder tumour (TURBT) using a wire loop diathermy violates the basic principle of oncological surgery, i.e. dissection through normal tissue. However, in the en bloc technique, the tumour is removed as a single specimen. We compared the quality of specimen and recurrence rate at three months (first check cystoscopy) in both the en bloc and conventional resection techniques. Methods: The subject accrual was done from June 1st, 2017 till June 30th, 2019 at a tertiary care hospital. Patients with newly diagnosed bladder tumour, solitary or multiple ‰¤ 3cm were included in the study. Patients with carcinoma in situ, prior TURBT, or muscle-invasive bladder cancer were excluded. Eighty-two patients were available for final analysis, 41 in each group. Results: Mean age, gender ratio, tumour features (grade, stage, median number, and size) were comparable in the two groups. Median Operative time [interquartile range- (IQR)] was 30 (25 - 39.5) minutes in the en bloc group as compared to 45 (33 - 63.5) minutes in the conventional group (p < 0.001). The detrusor muscle was seen at the base of the primary tumour in all 41 (100%) en bloc cases as compared to 23 (56 %) cases in the conventional group (p <0.001). Overall recurrence at the first surveillance cystoscopy was 17%, with an insignificant difference between the groups. Recurrence at primary site was 19.5% in conventional TURBT compared to en bloc resection (n = 1, 2.4%), (p = 0.013). Conclusion: En bloc resection decreases the recurrence rate at the primary site. En bloc TURBT is a safe technique, providing high-quality specimens for histopathological evaluation and reducing the need for the second TURBT. Keywords: En bloc TURBT; conventional TURBT; non-muscle-invasive bladder cancer; recurrence rate; detrusor muscle